Novel prior position determination approaches in particle filter for Ultra Wideband (UWB)-Based indoor positioning - Zhou, Ning; Lau, Lawrence; Bai, Ruibin; Moore, Terry (Wiley, 2021)
Filtering‐based indoor positioning using ultra wideband (UWB) requires known velocity to predict prior position in the prediction stage. Velocity can be obtained from an inertial measurement unit (IMU) sensor or the posterior state vector at the previous time stamp. Both methods have limitations when using them in practice. This paper proposes two novel velocity determination approaches, which use measurements to approximate velocity in a self‐contained way. They are integrated into particle filtering algorithms for prior position determination. The test result shows that the particle filter with the proposed approaches performs similarly to the Rao‐Blackwellized particle filter and slightly better than the particle filter with IMU. Compared with the standard particle filter, the particle filters with our proposed approaches achieve similar positioning accuracies with less computation time. Moreover, it is found that the integration of Angle‐of‐Arrival measurements in particle‐filter‐based positioning improves the 3‐D positioning accuracy by about 37.3% on average.